An equivalent circuit grid model for no-insulation HTS pancake coils. (13th March 2015) - Wang, Y; Song, H; Xu, D; Li, Z Y; Jin, Z; Hong, Z
Abstract: An equivalent circuit grid (ECG) model is proposed to analyse the time-varying characteristics of no-insulation (NI) ReBCO pancake coils. In the model, each turn of the coil is subdivided into fine elements in the azimuthal direction, and each element is equivalent to a circuit parameter. Then, the coil is equivalent to a circuit grid. A math model based on Kirchhoff's law is proposed to solve the circuit grid model. The distribution of the electrical current inside the NI coil is analysed for the charging and discharging process. A finite element method (FEM) model is coupled to calculate the magnetic field induced by the coil. To validate the model, a double pancake (DP) coil is fabricated by coated conductor ReBCO tapes. Charging and discharging tests are performed on the coil at 77 K. The results from simulations and experiments exhibit a good agreement. Then, this model is used for more studies on the current distribution inside the NI coil in the charging and discharging process. The charging and discharging delay of NI coil is analysed and explained by the model. The model can also be applied to partial insulated (PI) coils and magnets consisting of NI coils.